Controlled and Efficient Synthesis of Quinoline Derivatives from Morita–Baylis–Hillman Adducts by Palladium-Catalyzed Heck Reaction and Cyclization - Selvakumar, Kodirajan; Lingam, Kandapalam Arun Prasath; Varma, Rama Varma Luxmi; Vijayabaskar, Veerappan (Synlett, 2015)
An efficient synthesis of 2,3-disubstituted quinoline derivatives from easily accessible (het)aryl-substituted Morita–Baylis–Hillman (MBH) adducts was achieved by an approach involving a palladium-catalyzed Heck reaction and cyclization. This strategy converts the MBH adducts into α-benzyl β-keto ester derivatives that can cyclize into the corresponding quinolines in good yields.
Keywords: quinolines; cyclizations; catalysis; palladium; Heck reactions; tandem reactions